Effects of Dietary Supplementation With Enterococcus faecium and Clostridium butyricum, Either Alone or in Combination, on Growth and Fecal Microbiota Composition of Post-weaning Pigs at a Commercial Farm - Sato, Yoshiaki; Kuroki, Yasutoshi; Oka, Kentaro; Takahashi, Motomichi; Rao, Shengbin; Sukegawa, Shin; Fujimura, Tatsuya (Frontiers in Veterinary Science, 2019)
Lactic acid bacteria (LAB) and butyric acid bacteria (BAB) are commonly used as probiotics in swine production. However, their combined effect on post-weaning pigs has not been assessed. Therefore, here, we investigated the individual and combined efficacy of dietary Enterococcus faecium and Clostridium butyricum on the growth and gut microbiota of post-weaning pigs at a commercial farm. Four independent trials were conducted, in each of which five pens containing 30 pigs each were assigned to one of five treatments: C, basal diet; L, basal diet + live E. faecium; D, basal diet + heat-killed E. faecium; M, basal diet + C. butyricum; or L+M, basal diet + live E. faecium + C. butyricum. Each trial was conducted over a 90-day period that was divided into two phases (Phase 1, days 0–40 post-weaning; and Phase 2, days 40–90 post-weaning), with the probiotics being supplemented only during Phase 1. Ten pigs were randomly selected from each pen for body weight (BW) analysis and fecal samples were collected from five or six of these pigs. In addition, the fecal samples from one randomly selected trial were used for gut microbiota analysis. We found that pigs in the L, D, and L+M treatment groups had a significantly higher BW than those in C (p < 0.05) but pigs in the L+M treatment group had a similar BW to those in the L and M groups. Furthermore, there were no significant differences in alpha diversity among the treatments but the beta diversity (weighted UniFrac distances) showed distinct clustering patterns, with pigs in C having discrete microbiota from those in all of the probiotics treatment groups except D (C vs. L, q = 0.04; C vs. M, q = 0.06; C vs. L+M, q = 0.06). These findings indicate that dietary supplementation with live or heat-killed E. faecium enhances growth performance in pigs but there is no synergistic effect when E. faecium is used in combination with C. butyricum. Furthermore, the addition of live E. faecium and C. butyricum to the diet of pigs may change the structure of the gut microbiota.